2023
DOI: 10.1007/978-3-031-25588-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of Aggrecan: A New Perspective on Cartilage Biomechanics, Disease and Regeneration

Abstract: Articular cartilage is a hydrated macromolecular composite mainly composed of type II collagen fibrils and the large proteoglycan, aggrecan. Aggrecan is a key determinant of the load bearing and energy dissipation functions of cartilage. Previously, studies of cartilage biomechanics have been primarily focusing on the macroscopic, tissue-level properties, which failed to elucidate the molecular-level activities that govern cartilage development, function, and disease. This chapter provides a brief summary of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…To evaluate this chondrogenesis, ATDC5 cells were cultured in chondrogenic medium supplemented with CuS NPs, B2M-CuS NPs, or PBS. The synthesis and remodeling of Acan occurs at early stages of cartilage formation and remains low during the middle and late stages [59][60][61], while Col-2 expression is consistently high throughout the early and late stages of cartilage formation [62]. We found that Acan gene expression was significantly higher in chondrocytes co-cultured for 7 days with B2M-CuS and CuS NPs, as compared to the control group (Fig.…”
Section: In Vitro Induction Of Chondrogenesis By B2m-cus Npsmentioning
confidence: 60%
“…To evaluate this chondrogenesis, ATDC5 cells were cultured in chondrogenic medium supplemented with CuS NPs, B2M-CuS NPs, or PBS. The synthesis and remodeling of Acan occurs at early stages of cartilage formation and remains low during the middle and late stages [59][60][61], while Col-2 expression is consistently high throughout the early and late stages of cartilage formation [62]. We found that Acan gene expression was significantly higher in chondrocytes co-cultured for 7 days with B2M-CuS and CuS NPs, as compared to the control group (Fig.…”
Section: In Vitro Induction Of Chondrogenesis By B2m-cus Npsmentioning
confidence: 60%